AB1185 Sustained maintenance of adapted ACR pediatric response with canakinumab in patients with active systemic juvenile idiopathic arthritis. (23rd January 2014) - Quartier, P.; Anton, J.; Barash, J.; Berner, R.; Abrams, K.; Lheritier, K.; Kim, D.; Wulffraat, N.
Abstract : Background: Systemic juvenile idiopathic arthritis (SJIA) is a rare autoinflammatory disease. Phase 3 data showed canakinumab (CAN), a fully human selective anti-IL-1β monoclonal antibody, provided robust initial adapted ACRpedi response in SJIA patients (pts) following a single dose. Objectives: Demonstrate sustained efficacy of CAN in the maintenance of adapted ACRpedi response. Methods: This was a two-part Phase 3 study in SJIA pts (2-20 yrs; CAN naïve or rolled-over from earlier studies). Part 1 (P1), an open label, active treatment maximum 33 wk long period (including a max 20 wk corticosteroid [CS] dose reduction subpart) was followed by Part 2 (P2), a randomized, DB, placebo-controlled, event-driven period. In P1, pts received CAN sc (4mg/kg to 300mg max) every 4 wks. Primary endpoint for P1 was the proportion of pts on CS at study entry who were able to taper it. We present data for the secondary endpoints: maintenance of adapted ACRpedi30/50/70/90/100 criteria, number of active joints and physician's global assessment of disease activity (PGDA; 0-100 mm VAS) during P1. ACR response was assessed at Days 15, 29 and every 4 weeks thereafter. PGDA and number of active joints were assessed at these same visits and at Baseline (BL) and Day 3. Results: 177 pts (128 on CS; 49 steroid-free) entered P1, of which 100 pts (CAN, n=50; placebo, n=50) entered P2; most of the 77 pts who did not enter P2 were eligible (>ACR30 at Day 15) to enter an open-label extension study directly when they discontinued. Of 92 pts attempting CS taper according to pre-specified criteria, 57 (62%) were successful, representing 44.5% (57/128; p<0.0001) of all pts who entered the study on a CS. 42 of the 92 (46%) who attempted a CS reduction and 42/128 (33%) of those entered study on a CS completely discontinued the CS. At Days 15 and 57, 84% and 94% were responders (≥ACR30), 59% and 78% had a minimum ACR70, and 17% and 39% had an ACR100, respectively. During the CS tapering period of P1, the proportion of pts in each ACR category remained stable except for ACR100 category which decreased from 30% at the start to 16% at the end of the CS taper period. At the end of P1: 76% had a minimum ACR30, 63% had a minimum ACR70 and 34% had an ACR100. Median PGDA was 70mm at BL and improved to 30mm at the first post-BL visit on Day 3. It decreased to 5mm on Day 85, the start of the steroid tapering period, to 3mm (96% improvement) at the end of the taper period on Day 197 and was 7mm at the end of P1. Median no. of active joints decreased from 10 at BL to 2 at Day 15 (-75%) and 1 (-93%) at Day 57. The median no. active joints continued to remain low during the steroid taper period (1 at Day 85; 2 at Day 169). At the end of P1, the median active joint count was 1. In P1, 78% of pts had at least 1 AE, the most common being an infection, mostly involving the upper respiratory tract. SAEs were reported in 14 pts, mostly due to infection (7pts) and MAS (4pts). 1 fatal MAS case occurred in 1 pts on CAN in P1. Conclusions: CAN allowed for successful steroid tapering with sustained maintenance of high adapted ACRpedi response while demonstrating an acceptable safety and tolerability profile in pts with active SJIA. Disclosure of Interest: P. Quartier Grant/Research support from: Novartis, J. Anton Grant/Research support from: Novartis, Pfizer, Consultant for: Novartis, Roche, Paid Instructor for: Novartis, Roche, Abbot, Speakers Bureau: Novartis, Pfizer, Abbot, SOBI, J. Barash Grant/Research support from: Novartis, R. Berner Grant/Research support from: Novartis, K. Abrams Shareholder of: Novartis, Employee of: Novartis, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, D. Kim Shareholder of: Novartis, Employee of: Novartis, N. Wulffraat: None Declared